The Impact of Organizational Culture and Working Motivation on Performance of Employee: A Case Study at Government Organization - Ludin, Ismail; Mukti, Saepul; Rohman, Ibnu Saepul (International Ecsis Association, 2023)
An effective human resource management strategy, which focuses on employee development, can help an organization gain a competitive advantage and achieve its long-term goals. This research aims to determine the influence of organizational culture and work motivation on the performance of employees of the Department of Cooperatives SMEs, Industry and Trade in Purwakarta Regency. This research is quantitative descriptive research, the sampling technique used is stratified random sampling. The number of samples taken from respondents, namely employees of the Department of Cooperatives SMEs, Industry and Trade in Purwakarta Regency, was 80 participants. Instrument testing in this research is validation testing and reliability testing. Meanwhile, data analysis techniques use linearity tests, normality tests, partial hypothesis tests, simultaneous tests. The results of this research show that organizational culture and work motivation variables have a positive effect on employee performance. The variables of organizational culture and work motivation have a positive effect on the performance and the results of this research show that the variables of organizational culture and work motivation have a positive and significant effect on the performance.